PENGARUH CARA PENAMBAHAN ENZIM GLUKOAMILASE DAN ION LOGAM ALKALI DAN ALKALI TANAH PADA PROSES SAKARIFIKASI PATI SAGU - A. T. Karossi; Agus Muchliawan; Linar Z.Udin; A. Sidik (Research Center for Chemistry - LIPI, 1995)
Production of glucose syrup enzymatically employs both alpha-amylase and glucoamylase. Alpha amylase acts during liquifaction while glucoamylase in the saccharification process. In the present study the glucoamylase was obtained from Rhyzopus oryzae fermentation for five days using 4 liter scale LKB fermentor. The influence of single stage and multiple stage additions of glucoamylase on alpha amylase liquified sago starch indicated no significant difference on the saccharification. The presence of 0.2 - 0.8 mM Li+, Na+, K+, Mg++, Ca++ and-Bar+ salts enchanced the glucoamylase activity whereas at the level of 1 mM they acted as inhibitors. The results of HPLC analysis of the saccharification product showed that the glucoamylase hydrolysed 83.3% of the sago starch yielding free glucose.